2006
DOI: 10.1002/polb.20857
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of Nafion and titania/Nafion composite membranes for polymer electrolyte membrane fuel cells

Abstract: Measurements of the mechanical and electrical properties of Nafion and Nafion/titania composite membranes in constrained environments are reported. The elastic and plastic deformation of Nafion-based materials decreases with both the temperature and water content. Nafion/titania composites have slightly higher elastic moduli. The composite membranes exhibit less strain hardening than Nafion. Composite membranes also show a reduction in the long-time creep of $40% in comparison with Nafion. Water uptake is fast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
181
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 232 publications
(190 citation statements)
references
References 45 publications
(50 reference statements)
5
181
0
1
Order By: Relevance
“…This relationship is referred to as non-affine deformation and has been shown to occur for PFSA membranes by a number of studies in literature [11,[18][19][20][21][22]29,[33][34][35]. Despite the growing body of literature on the sorption behavior [7,8,10,24,34,35,38,40,[44][45][46][47][48][49][50] and nano-structural modeling and characterization [11,13,[17][18][19][20][21][22]28,29,31,[33][34][35][36]39,49,51,52] of PFSA ionomers, the relationship between the water uptake and nanostructure, temperature, mechanical properties and membrane pretreatment is not well established. Understanding of these issues requires a general, yet fundamental model, which is the subject of this study.…”
mentioning
confidence: 99%
“…This relationship is referred to as non-affine deformation and has been shown to occur for PFSA membranes by a number of studies in literature [11,[18][19][20][21][22]29,[33][34][35]. Despite the growing body of literature on the sorption behavior [7,8,10,24,34,35,38,40,[44][45][46][47][48][49][50] and nano-structural modeling and characterization [11,13,[17][18][19][20][21][22]28,29,31,[33][34][35][36]39,49,51,52] of PFSA ionomers, the relationship between the water uptake and nanostructure, temperature, mechanical properties and membrane pretreatment is not well established. Understanding of these issues requires a general, yet fundamental model, which is the subject of this study.…”
mentioning
confidence: 99%
“…[335] is suggesting that aging has no influence on the water transport coefficient despite other studies [220][221][222][223][224][228][229][230] where a significant change in the physical properties of aged membranes was detected. However, none of these studies have addressed the effect of water transport mechanism on membrane durability.…”
Section: Mea and Gdl Structurementioning
confidence: 54%
“…Statterfield et al [223] suggested the addition of Ttitanium oxide (titania) for improving the elastic and plastic deformation behaviour of Nafion under changes in temperature and water concentration. These composite membranes (e.g.…”
Section: Membrane Swellingmentioning
confidence: 99%
See 1 more Smart Citation
“…For the membrane degradation, according to numerous experimental results, there are chemical degradation [8], mechanical degradation [9] and thermal degradation [10], which are strongly dependent on operating conditions such as temperature, humidity, freezethaw cycling, transient operation, and start-up/shut-down [2]. For the GDL degradation, to date, only a limited number of studies have focused on the degradation mechanisms of GDL or on the relationship between GDL properties and PEMFC performance decay, but its degradation includes the physical degradation [11], so called the mechanical and thermal degradation, and chemical and electrochemical degradation [12].…”
mentioning
confidence: 99%